General pedagogical knowledge among pre-service vocational teachers : measurement and development during teacher education - Abele, Stephan [Verfasser]; Vogel-Blaschka, Diana [Verfasser]; Leon, Andreas [Verfasser]; Beck, Marlen [Verfasser]; Bärbel Fürstenau [Verfasser] (My University, 2025)
„The relevance of general pedagogical knowledge (GPK) for vocational teachers is internationally recognised but has not yet been systematically investigated. In this study, the GPK of pre-service vocational teachers is analysed using an established GPK test. Structural equation modelling was used to analyse the test's psychometric quality and GPK development using a cohort-sequential design (N = 374). The results indicate that the test measures GPK one-dimensionally and that there is substantial GPK development among pre-service teachers (d = .68–1.63). Our study suggests that previous studies may have been biased (e.g., because they assumed the test measures GPK multidimensionally).” (authors’ abstract; BIBB-Doku)
Keywords: P 3.2.3 Lehrer; 370; Berufsschullehrer; Lehrerausbildung; Vorbereitungsdienst; Pädagogisches Wissen; Modellierung; Messung